Vol. 4 No. 2 Penerapan Model Pembelajaran Kooperatif Tipe Team Games Tournament untuk Meningkatkan Hasil Belajar Siswa - Farihah Hesya, Aay; Wahidah, Iis Isni (Ta'lim: The Islamic Religious Educational Journal, 2025)
Abstract Basically, Islamic Religious Education (PAI) teachers have a strong desire to enhance students' abilities and understanding, especially in learning about the Hajj pilgrimage, by applying appropriate learning models. However, based on preliminary observations, the researcher found that the teacher only used direct instruction or lecture methods. The use of direct learning models was considered less effective, as it caused boredom, leading students to lose focus and become disengaged during lessons, which in turn impacted their learning outcomes. This study aims to investigate how the implementation of the cooperative learning model, specifically the Team Games Tournament (TGT) type, can improve the learning outcomes of fifth-grade students on the topic of Hajj at SDN Sukasari Kidul I. The TGT model is one of the cooperative learning models that fosters enthusiasm, nurtures a sense of responsibility, and enhances motivation through games and tournaments. The method used in this study is Classroom Action Research (CAR), carried out in several cycles. The research was conducted at SDN Sukasari Kidul I, with the research subjects being 13 fifth-grade students. Data collection techniques involved observation sheets and test sheets. The data were analyzed using descriptive analysis. Based on data processing and analysis, it can be concluded that the implementation of the cooperative learning model type Team Games Tournament (TGT) effectively improved the learning outcomes of fifth grade students at SDN Sukasari Kidul I. This is evidenced by a 77% increase in students’ learning mastery, along with improvements in collaboration, participation, confidence, and discipline. Through this research, the author hopes that the school and its educators will consider implementing the cooperative learning model type Team Games Tournament (TGT) in other subjects and learning programs. Keywords: Cooperative Learning Model, TGT, PAI, Learning Outcomes